Participation of the C-terminal propeptide procollagen type I in the formation of cardiofibrosis in patients with myocardial infarction with preserved left ventricular ejection fraction - A. V. Osokina; V. N. Karetnikova; O. M. Polikutina; A. V. Ivanova; T. B. Pecherina; O. V. Gruzdeva; Yu. A. Dyleva; A. N. Kokov; N. K. Brel; O. L. Barbarash (Российский кардиологический журнал, 2021)
Aim. To study the dynamics of procollagen type I carboxy-terminal propeptide (PICP) with an assessment of potential associations with cardiac fibrosis (CF) and diastolic dysfunction (DD) of the left ventricle (LV) during the hospitalization and one year after ST segment elevation myocardial infarction (STEMI).Material and methods. The study included 120 patients with STEMI. There were following inclusion criteria: diagnosis of STEMI (2015 European Society of Cardiology guidelines); Killip £III acute heart failure (AHF); signed informed consent; patient age >18 years old. There were following exclusion criteria: STEMI due to percutaneous coronary intervention or coronary artery bypass grafting; Killip IV AHF; patient age >80 years; clinically significant comorbidities; death of the patient during the first day of hospitalization. On the 1st, 12th day of the disease and after a year all patients underwent echocardiography and the PICP concentration was determined. One year after myocardial infarction, contrast-enhanced cardiac magnetic resonance imaging was performed to assess CF. In the analyzed group of patients, on day 1 of STEMI, mean values of LV ejection fraction (EF) in the range of 40-49% were observed in 3 (2,5%) patients, LVEF <40% — in 31 (26%), LVEF ≥50% — in 86 (71,7%). The final analysis was performed on a sample of patients with preserved LVEF (n=86) (71,7%).Results. On the first day of myocardial infarction, signs of DD were noted in 25 (29,1%) patients, while after 1 year, their number increased by 9 (10%) and amounted to 34 (39,5%) patients. In 15 (17,6%) people, worsening of myocardial systolic dysfunction was noted. Patients with a CF ³16% had the highest PICP expression on the first day of the disease. CF ≥16% one year after STEMI with preserved EF is associated with PICP concentration on day 1 of the disease. In addition, multidirectional correlations were revealed between the CF ≥16% and parameters of LV diastolic function (e’, mean pulmonary artery pressure, E/e’).Conclusion. Determination of the PICP concentration on the 1st day of myocardial infarction will allow early identification of patients at risk of CF one year after STEMI with preserved EF.